Cardiac function in children with congenital diaphragmatic hernia: cardiac strain at birth and at 2–5 weeks of age - Tydén, Katarina Övermo; Magnusson, Kerstin; Burgos, Carmen Mesas; Jonsson, Baldvin; Nordenstam, Felicia (Frontiers in Pediatrics, 2025)
IntroductionNeonates with congenital diaphragmatic hernia (CDH) often present with pulmonary hypertension and various forms of cardiac dysfunction, affecting right or left ventricle or both. Although pulmonary hypertension typically improves over time, some children experience long term pulmonary hypertension. There is limited understanding of cardiac function recovery. The authors hypothesized that cardiac function in the CDH population would remain impaired during the first 2–5 weeks of life compared with in a control group.MethodThis prospective observational cohort study included 40 newborns with CDH and 40 controls born in 2021–2024 and cared for at Karolinska University Hospital, Stockholm, Sweden. The first study echocardiograms were performed between 6 and 24 h of age. Subsequently, 23 of the 40 CDH cases were also examined at 2–5 weeks of age. Left ventricular longitudinal strain (LV LS), right ventricle free wall strain (RVFWS), left atrial reservoir strain (LASr), right atrial reservoir strain (RASr), and conventional echo parameters were analyzed.ResultsNewborns with CDH had reduced cardiac function measured with LV LS [mean −14.7% (standard deviation 4.6) vs. −18.8% (2.7), p < 0.001], RVFWS [−13.9% (4.2) vs. −22.4% (4.8) p < 0.001], LASr [22.8% (9.3) vs. 33.9% (8.2), p < 0.001], and RASr [21.8% (6.9) vs. 37.6% (9.2), p < 0.001], compared with controls. Cardiac strain had improved for all subjects at the age of 2–5 weeks. However, the cases with CDH still had lower strain than the controls.ConclusionCardiac function measured as strain was reduced in newborns with CDH compared with in a control group. Although their cardiac function improved over time, it remained lower compared to the control group at 2–5 weeks of age.